PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS (Studi kasus pada perusahaan Aneka Industri yang terdaftar di Bursa Efek Indonesia periode 2013-2016) - TITIN APRIATI; M.Agus Salim; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research was conducted to determine the effect of sales growth, working capital turnover and liquidity to profitability. The research was conducted at different companies in Indonesia Stock Exchange (BEI). Determination of sample in this research using purposive sampling method. The number of samples is 16 companies after the outliers of 22 companies. Data analysis using multiple linear regression analysis. The magnitude of the influence of independent variables can affect the variable of 17.5% and the remaining 82.5% by other factors not included into the research model. The result showed that the variable of sales growth on the profitability of the variable of working capital turnover and the uneven liquidity to profitability.Keywords: Growth of sales, Working capital turnover, liquidity and Profitability